X-Y converter family: A new breed of buck boost converter for high step-up renewable energy applications - Mahajan, S.B.; Sanjeevikumar, Padmanaban; Wheeler, Patrick; Blaabjerg, Frede; Rivera, Marco; Kulkarni, Rishi (2016)
A new breed of a buck boost converter, named as the XY converter family is proposed in this article. In the XY family, 16 topologies are presented which are highly suitable for renewable energy applications which require a high ratio of DC-DC converter; such as a photovoltaic multilevel inverter system, high voltage automotive applications and industrial drives. Compared to the traditional boost converter and existing recent converters, the proposed XY converter family has the ability to provide a higher output voltage by using less number of power devices and reactive components. Other distinct features of the XY converter family are i) Single control switch ii) Provide negative output voltage iii) Non-isolated topologies iv) High conversion ratio without making the use of high duty cycle and v) modular structure. XY family is compared with the recent high step-up converters and the detailed description of XY converter family and its topologies are presented. The simulation results are provided and it confirms the feasibility, functionality and validity of the concepts of the proposed XY converter family.